Antimicrobial and Antioxidant Activity of Pomegranate Peel Extracts Obtained by Sequential Extraction Method - Abdealsiede, Missa Mohammed Saleh; Alrasheid, Ayat Ahmed; Ali Omar, Mei Musa; Elbashir, Abdalla Ahmed (Asian Journal of Pharmaceutical Research and Development, 2020)
Punica granatum L. (Pomegranate) is a plant belongs to Lythraceae family. The objective of this study was to evaluate the antimicrobial activity of petroleum ether, chloroform , acetone, ethyl acetate and ethanol extracts from the peel fruit of Punica granatum against standard microorganism. This plant has been used as a traditional treatment for several diseases such as microbial infections. Extracts were evaluated for their effectiveness against four bacterial strains including both Gram-positive (Bacillus subtilis and Staphylococcus aureus) and Gram-negative (Escherichia coli and Pseudomonas aeruginosa) bacteria as well as fungal species (Candida albicans and Aspergillus niger) using disc diffusion method. The ethyl acetate, acetone and petroleum ether extracts showed higher antibacterial activity than the chloroform and ethanol extracts with inhibition zone ranged between (7-16 mm). The petroleum ether and chloroform extracts showed the higher antifungal activity compared with the other extracts, the diameter inhibition zone ranged between (11-16 mm). The antioxidant potential of peel extracts was determined on the basis of their scavenging activity of the stable 1, 1-diphenyl-2-picryl hydrazyl (DPPH) free radical and 2,2'azino-bis(ethyl benzthiazoline -6-sulfonic acid (ABTS+). All extracts showed high antioxidant activity . The highest result of antioxidant activity by DPPH scavenging assay was in acetone extract (89.40%), but high result by ABTS in ethanol extract (72.07%). KEYWORDS: